2017
DOI: 10.14203/widyariset.3.1.2017.47-54
|View full text |Cite
|
Sign up to set email alerts
|

THERMOMECHANICAL TREATMENT PROCESS OF α/βTi-6Al-6Mo ALLOY AS NEW ALTERNATIVE MATERIALS FOR BIOMEDICAL APPLICATION

Abstract: Article history

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…The AFM probe couldn't generate the image of the surface due to the extreme difference of the plate's surface contour. Molybdenum is selected due to its high capability as a beta phase stabilizer and more fair price compared to vanadium [9]. The previous experiment has shown that the Ti-Al-Mo exhibited both alpha and beta phases with hardness value ranges from 35 to 40 HRC in various thermomechanical conditions [9].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The AFM probe couldn't generate the image of the surface due to the extreme difference of the plate's surface contour. Molybdenum is selected due to its high capability as a beta phase stabilizer and more fair price compared to vanadium [9]. The previous experiment has shown that the Ti-Al-Mo exhibited both alpha and beta phases with hardness value ranges from 35 to 40 HRC in various thermomechanical conditions [9].…”
Section: Resultsmentioning
confidence: 99%
“…Molybdenum is selected due to its high capability as a beta phase stabilizer and more fair price compared to vanadium [9]. The previous experiment has shown that the Ti-Al-Mo exhibited both alpha and beta phases with hardness value ranges from 35 to 40 HRC in various thermomechanical conditions [9]. A previous study also suggested that solutiontreated followed by air quenching promotes the hardness value of Ti-Al-Mo compared to water quenching due to higher alpha phase intensity compared to alpha' (α') and beta (β) phases [10].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The most commonly known type α+β titanium alloy is Ti-6Al-4V (Extra Low Interstitial-ELI), where Al acts as an α phase stabilizer and V as a β phase stabilizer. The next research that has been carried out is the development of Ti6Al6Mo and Ti6Al6Nb titanium alloys where the elements Nb and Mo are used to replace the element V. However, the resulting final elastic modulus is still relatively high at around 115 GPa [15,17,21].…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%